Application of modern agronomic and biotechnological strategies to valorise worldwide globe artichoke (Cynara cardunculus L.) potential - an analytical overview - Aneta Grabowska; Gianluca Caruso; Ali Mehrafarin; Andrzej Kalisz; Robert Gruszecki; Edward Kunicki; Agnieszka Sękara (Italian Journal of Agronomy)
The globe artichoke [Cynara cardunculus L. var. scolymus (L.) Fiori], an ancient vegetable originated in the Mediterranean Basin, is currently cultivated in many regions of the world under a perennial cycle or as an annual crop, with the first method being more widespread globally. The growing importance of globe artichoke as modern functional food as well as a source of pharmaceuticals has raised new issues that all producers have to face; hence the necessity of contemporaneous development of new centres of production and new technologies application in traditional regions of growing which can complement the global market. This review is focused on development of globe artichoke technology of production in recent several years which meet the diversified requirements of global and local markets. We considered the recent literature to highlight specific applications of modern farming practices and plant breeding along with genetic variation to globe artichoke production system as well as to postharvest management in order to enhance the value added of this commodity. The latter targets are mainly addressed to particular regions of the world and they are based on farmers knowledge, equipment, scale and methods of production, processing, final market. Our reports are focused on sustainable and environmentally friendly methods which can improve the profitability of production as well as product’s quality and quantity traits. We discussed the balanced mineral application which can precisely affect the yield chemical composition, attractiveness and shelf life of globe artichoke heads as well as create the opportunities to attain standardised by-products, valuable on the market of health and convenient food. Further topics were developed, such as introduction of seed propagation, intercropping, grafting, flowering induction, postharvest treatments as linked to different regions and conditions of production. Precise selection of modern management practices was recognised as a main goal to fulfil the requirements of local and global market for fresh, processed and new potential globe artichoke products.